(untitled) (Conferencea, 2023)
This article describes the existing system of government and its legal foundations under the Ashtarkhanids, a new dynasty that ascended the throne of the Bukhara Khanate at the beginning of the 17th century. Under the Ashtarkhanid dynasty, the system of state administration was carried out in the same way as under the Shaybani dynasty, and the main differences in administration under the two dynasties were noted. The situation in Bukhara, Samarkand, Oratepa, Guzor, Shakhrisabz regions is mainly mentioned.